Gender peculiarities of epidemiology and clinical course in patients with psoriasis associated with arterial hypertension - G. I. Makurina; V. P. Fedotov; V. A. Vizir (Zaporožskij Medicinskij Žurnal)
The combination of psoriasis and hypertension influences on the clinical course of both diseases.